Five-year experience with screening electrocardiograms in National Collegiate Athletic Association Division I athletes - Fuller, C.; Scott, C.; Hug-English, C.; Yang, W.; Pasternak, A. (Clinical Journal of Sport Medicine, 2016)
Objective: (1) Compare rates of abnormal screening electrocardiograms (ECGs) using updated criteria compared with older criteria. (2) Compare rates of abnormal ECGs by ethnicity. (3) Evaluate ability of ECG criteria to detect the predicted number of athletes with previously undetected cardiovascular abnormalities.